Contextualization of Religion and Entrepreneurial Performance: A Lens of Buddhist Small Business Entrepreneurs - Mahadewi, Lufina; Surachman, Surachman; Hadiwidjojo, Djumilah; Indrawati, Nur Khusniyah (Frontiers in Psychology, 2022)
This study explores the manifestation of Buddhism conception in underlying entrepreneurial performance. The study is a qualitative research approach with a development direction comes from successful small business Buddhist entrepreneurs in Bekasi, Indonesia. The interpretive paradigm is used to interpret social life in the reality of successful small business Buddhist entrepreneurs on entrepreneurial performance. Data collection using in-depth interviews with small business Buddhist entrepreneurs in an open-ended format. Stages of data analysis using domain analysis, taxonomy analysis, component analysis and theme analysis. The finding indicates that religion acts as an institution that legitimizes the formation of entrepreneurial performance. The performance of small business Buddhist entrepreneurs is manifested in the form of management performance in economic or material achievements, religious observance in a broad socio-economic context in the relationship of three aspects of human life, namely individual, social and environmental as a form of entrepreneurial practice based on Buddhist values. This research revealing the embodiment of social responsibility for small business Buddhist entrepreneurs which is reflected in entrepreneurial performance through the manifestation of religious values. The findings provide theoretical relevance in institutional theory.